The Economics of Remanufacturing Under Limited Component Durability and Finite Product Life Cycles - Geyer, Roland; Van Wassenhove, Luk N.; Atasu, Atalay (Management Science, 2007)
This paper models and quantifies the cost-savings potential of production systems that collect, remanufacture, and remarket end-of-use products as perfect substitutes while facing the fundamental supply-loop constraints of limited component durability and finite product life cycles. The results demonstrate the need to carefully coordinate production cost structure, collection rate, product life cycle, and component durability to create or maximize production cost savings from remanufacturing.